Higher blood aldosterone level in metabolic syndrome is independently related to adiposity and fasting plasma glucose - Chiang, Jui-Kun (Cardiovasc Diabetol, 2015)
BACKGROUND: Hypoadiponectinemia is a well-known state associated with metabolic syndrome (MetS) and insulin resistance (IR). Recently aldosterone has been highly associated with high blood pressure, and may thus be a possible biomarker for MetS and IR. In this study, we investigate the association of aldosterone with MetS and IR, and compare it with that of adiponectin. METHODS: In this cross-sectional study, we recruited 556 women receiving physical examinations at a general hospital in central Taiwan. At the time of examination, we collected data on various demographic and physical characteristics and measured blood levels of aldosterone, adiponectin and a variety of metabolic factors. Multiple linear regression analysis was performed using adiponectin or aldosterone as the dependent variables. RESULTS: We found an inverse correlation between blood adiponectin and aldosterone (γ = −0.11, P = 0.009). Adiponectin levels were lower and aldosterone levels higher in women with MetS that those without (8.1 ± 0.4 vs. 11.5 ± 0.2 μg/mL, P < 0.001 and 691 ± 50 vs. 560 ± 11 pmol/L, P = 0.013, respectively), as they were in women with and without IR (adiponectin 10.4 ± 0.5 vs. 11.3 ± 0.2 μg/mL, P = 0.003 and aldosterone 635 ± 31 vs. 560 ± 11 pmol/L, P = 0.022). Although aldosterone was significantly related to body fat %, fasting plasma glucose and serum creatinine levels, the relationship between adiponectin and aldosterone was not obvious after adjustment in the multivariate analysis. CONCLUSION: Although aldosterone was related to metabolic factors, including body fat % and fasting plasma glucose in our female subjects, the relationship between aldosterone and adiponectin remains unclear.